Graduates with competencies and leadership sought by employers - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
KUANTAN, 17 March 2022 - Graduates with high competencies by mastering various languages, have self-confidence, can communicate well and have the ability to operate high-tech equipment have the advantage of gaining a place in the job market.